The History of the Formation of Physical Culture - Sarbinaz Kutlymuratova (Antis Publisher, 2024)
The necessary physical qualities, skills and abilities for people were acquired in the process of their direct labor activity. Only young people learned to some extent from older people how to make and work with the simple tools available at that time and how to protect them from wild animals.